Il tempo sospeso del progetto : the New Mies Memorial Library. Illinois Institute of Technology, Chicago - Renzullo, Lorenzo (TeA / Teaching Architecture, 2023)
The publication collects the results of a didactic research activity carried out in the field of the degree theses in Architectural and Urban Design, discussed in the academic years 2020/21, in the Course in Architecture (Arc5UE) and in the master's degree course in Architecture - Architectural Design (MAPA/ACTA), at the Department of Architecture of the University of Naples "Federico II". The common theme is "THE NEW MIES MEMORIAL LIBRARY" and the case study is the Illinois Institute of Technology Campus in Chicago, USA. The pretext of this research pertains to an international architectural design competition with the theme of the "New Mies Memorial Library". The legacy of the major "masters" of Modern architecture has always represented a test ground to confront and experiment and, in this sense, the purpose of this research is to broaden the cultural and methodological boundaries that directly affect the reasons and possibilities of the architectural project on this paradigmatic production of the Modern. The projects, with the support of expert professors in and technology disciplines, develop possible design responses, starting from the analysis of the specific conditions of the place, particularly the current North American Campus, to look at the architectural project, in this exemplary case, as the result of a conscious knowledge, open to dialogue and capable of implementing an adequate reflection.